Meridiolithothamnion atlanticum gen. et sp. nov. (Hapalidiales, Rhodophyta), a rhodolith-forming non-geniculate coralline alga from Brazil and offshore the northern Gulf of Mexico - Leão, Luis Alfredo S. De; Richards, Joseph L.; Bahia, Ricardo G.; Fredericq, Suzanne; Pereira, Renato Crespo (Phytotaxa, 2025)
DNA sequence analysis of plastid-encoded psbA and rbcL loci of rhodolith-forming specimens of Hapalidiales from Brazil and the NW and NE Gulf of Mexico revealed them to belong to an unnamed species in a herein newly described genus named Meridiolithothamnion atlanticum gen. et sp. nov. that is sister to Boreolithothamnion (Hapalidiaceae). Detailed morpho-anatomical examination supports its taxonomic uniqueness, highlighting specific combination of vegetative and reproductive structures, including distinctive balloon-like basal pore canal cells within the tetrasporangial conceptacles. This genus contributes to understanding the biodiversity and biogeographic linkages of marine algae across the Western Atlantic, suggesting connectivity between Brazil and Gulf of Mexico regions.